THU0369 Costs of Early Spondyloarthritis: Estimates from the First Three Years of the Desir Cohort. (9th June 2015) - Harvard, S.; Guh, D.; Bansback, N.; Richette, P.; Dougados, M.; Anis, A.; Fautrel, B.
Abstract : Background: The costs of spondyloarthritis (SpA) from health resource use (HRU) and productivity loss (PL) have chiefly been evaluated among patients with established disease. Costs among early SpA patients have not been well described. Objectives: To describe trends in HRU and PL costs over the first 3 years of the DESIR cohort of early SpA patients. Methods: DESIR is a longitudinal cohort of 708 patients with early (<3 years) inflammatory back pain suggestive of SpA. Follow-ups were every 6 months in the first 2 years and every year thereafter. This analysis included patients with all post-baseline follow-ups and complete cost data. French public data were used to determine unit costs for HRU (hospital services, medical workups, health practitioner visits, and medications) and to estimate the value of PL. Hospital services costs were estimated by assigning 'best-fit' Diagnosis-Related Groups (DRG) to hospitalizations, surgeries and emergency visits and then explored in sensitivity analyses (SA) with a range of related DRGs. Year 1 and 2 totals were calculated by combining 6- and 12-month and 18- and 24-month follow-ups, respectively. Year 3 totals were based on costs reported at month 36. Results: The analysis included 496 patients. By Year 3, 45% of patients satisfied the ASAS imaging criteria and 60% satisfied the ASAS clinical criteria; 73% satisfied either. Across Years 1-3, 26-29% of patients incurred costs from hospital services, 80-84% from medical workups, and 91-97% from health practitioner visits. Each year, >90% of patients had medication costs, with non-steroidal anti-inflammatory drugs used by most patients (88%, 79%, 68% in Years 1, 2, 3). Biologics use increased from 30% in Year 1 to 36% in Year 3. The mean (median) total cost per patient was € 7270 (€ 2629) in Year 1, € 7420 (€ 2950) in Year 2, and € 6510 (€ 2248) in Year 3 (estimates not substantially affected by SA). Patients with PL decreased yearly, from 48% to 38% to 30% in Years 1, 2, 3. In all years, the greatest cost-driver was medication, increasing from € 3432 to € 4283 to € 4578 in Years 1, 2, and 3, representing 48%, 58%, and 70% of total costs. Biologics accounted for over 90% of medication costs. In Years 1 and 2, the second greatest cost-driver was PL, at € 2241 (31%) and € 1550 (21%) of costs; in Year 3 PL costs decreased to € 618 (9% of all costs). Physiotherapy consumed over 36% of health practitioner costs each year. Non-biologics users had 3-year mean total costs of € 6682 (sd=9358), compared to € 42, 691 (sd=21, 601) among biologics users. Overall, patients on biologics accounted for 75% of all costs in the cohort. Conclusions: Biologics are the greatest cost-driver among early SpA patients. We observed a decline in PL over three years. A cost-effectiveness analysis of biologics among SpA patients is required to better understand their value. Acknowledgements: We acknowledge the contributions of the DESIR Cohort and Scientific Committee Disclosure of Interest: None declared